2017
DOI: 10.9745/ghsp-d-16-00281
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Women's Contraceptive Preferences With Their Choices in 5 Urban Family Planning Clinics in Ghana

Abstract: Women's method choice largely matched their stated desired duration of effectiveness but not their desires to avoid certain side effects. While most women reported they were counseled about side effects, many fewer reported being specifically counseled about common menstrual side effects with their chosen method, including side effects the women said would cause them to stop using the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
3
20
1
1
Order By: Relevance
“…Bleeding profiles differ across methods, and women's preferences should inform a tailored counseling approach and be incorporated into deciding which method to select. 22 ABSENCE OF MENSES – If you are using a hormonal method, ABSENCE OF MENSES does not mean that you are pregnant. Providers should reassure users of hormonal contraception that they should not assume absence of menstrual bleeding is, by itself, a sign of pregnancy.…”
Section: Proposed Toolmentioning
confidence: 99%
See 2 more Smart Citations
“…Bleeding profiles differ across methods, and women's preferences should inform a tailored counseling approach and be incorporated into deciding which method to select. 22 ABSENCE OF MENSES – If you are using a hormonal method, ABSENCE OF MENSES does not mean that you are pregnant. Providers should reassure users of hormonal contraception that they should not assume absence of menstrual bleeding is, by itself, a sign of pregnancy.…”
Section: Proposed Toolmentioning
confidence: 99%
“…Bleeding profiles differ across methods, and women's preferences should inform a tailored counseling approach and be incorporated into deciding which method to select. 22 …”
Section: Proposed Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues need to be foregrounded in counselling for this group of women. [9,10] Encouragingly, Pillay et al [3] found that many women had negotiated implant insertion, and indeed removal, with their partners. Others chose clandestine use, allowing them to use the implant without knowledge of their partners.…”
Section: Counselling and Choicementioning
confidence: 99%
“…As an example, our study team interviewed women in Ghana's two largest cities to determine the extent to which women were receiving the contraceptive method of their choice (Rominski et al. ; Rominski et al. ).…”
mentioning
confidence: 99%